A Comprehensive in Silico Analysis of Regulatory SNPs of Human CLEC7A Gene and Its Validation as Genotypic and Phenotypic Disease Marker in Recurrent Vulvovaginal Infections - Kalia, Namarta; Kaur, Manpreet; Sharma, Sujata; Singh, Jatinder (Frontiers in Cellular and Infection Microbiology, 2018)
Recurrent Vulvovaginal infections (RVVI) are the commonly reported microbiological syndrome affecting millions of women globally. Various molecules of innate immune system are instrumental in clearance of these microbial pathogens, thus suggested as one of the most important contributing factor in determining the disease outcome. Dendritic cell-associated C-type lectin-1 (Dectin-1) is an important molecule of innate immunity that is primarily known for its role in antifungal defences. However, role of dectin-1 in recognition of other pathogens is also documented. The intracellular expression of dectin-1 was shown to be up-regulated by Mannose Binding Lectin (MBL)-mediated opsonophagocytosis of pathogens. Dectin-1 is encoded by CLEC7A, postulated to be a candidate gene in modulating risk of developing RVVI. In this study, we identified CLEC7A causal variants using in silico analysis. To assess their impact on susceptibility to RVVI, these causal variants along with serum dectin-1 levels (sDectin-1) were investigated using polymerase chain reaction-restriction fragment length polymorphism (PCR–RFLP) and Enzyme Linked Immnosorbent Assay (ELISA) respectively, under a case-control design. Furthermore, effect of these polymorphisms was also assessed on sMBL levels. In silico analysis revealed 9 putative functional conserved SNPs of CLEC7A. Association analysis revealed a significantly lower risk of developing RVVI and its types in carriers of CLEC7A rs3901533 G allele and its homozygous genotypes (p<0.05). The heterozygous genotype was associated with significant protection against RVVI (p=0.004). Haplotypes GGG and GTA showed significant protection against RVVI (p<0.0001; p=0.0003), Bacterial Vaginosis (p=0.03; p=0.002), Vulvovaginal Candidiasis (p=0.03; p=0.01) and Mixed Infections (p=0.007; p=0.04). Mean sDectin-1 levels were significantly high in RVVI and its types compared to controls (p<0.05). Further, genotype-phenotype stratification showed significant differences within/between cases groups and controls. The CLEC7A rs3901533 polymorphism was also found to be associated with sMBL levels. The present study contributed novel insights into the role of dectin-1 in RVVI. CLEC7A rs3901533 polymorphism and high sDectin-1 levels along with low sMBL levels were found to be associated with RVVI susceptibility. Thus, screening of women with RVVI for these novel associations may lead to better diagnosis and treatment. Also genotyping method used in this study constitutes a simple and reliable assay.